The Application of Problem Based Learning Model Assisted by Audio-Visual media to improve Social Science Outcomes in 4th grade 5 Selat Hulu Elementary School - Chandra Anugrah Putra; Dina Dwi Lestari (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: The nature of Social Science learning has consequences for the teaching and learning process which is dominated by an expository approach, especially teachers using the lecture method while students are less involved or tend to be passive. Aim: Describe social studies learning activities using Problem Based Learning learning model assisted by audio visual media, Know the improvement of social studies learning outcomes through Problem Based Learning learning model assisted by audio visual media. Method: The object of this research is fourth grade students of 5 Selat Hulu Elementary School, Selat District, Kapuas Regency, Central Kalimantan, totaling 25 students. The method used in this research is Classroom Action Research. Results and Dıscussion:The results showed that: 1. There is a good increase in teaching and learning activities used in social studies learning by using the Problem Based Learning learning model assisted by audio-visual media in cycle I the average score value of the teacher's activity aspect is 3.1 then in cycle II becomes an average score of 3.7. Furthermore, the increase in student learning activities in cycle I obtained an average score of 3 then in cycle II the average score of 3.4 from the results of observers. 2. There is an increase in social studies learning outcomes by using the Problem Based Learning learning model assisted by audio visual media, namely classical completeness in cycle I 64% then in cycle II 100%.